TINGKAT PENGETAHUAN MAHASISWA KEPERAWATAN TINGKAT 2 TENTANG AKTIVITAS FISIK DI ITSK RS DR SOEPRAOEN MALANG - Maulana Arif Murtadho; Dion Kunto, Riki Ristanto (Jurnal Kesehatan, 2023)
Introduction: In the world of health, it is considered lazy to move, or what is commonly called a sedentary lifestyle. This condition will definitely cause problems if it lasts for a long time due to reduced or even decreased physical activity or movement. Method: This type of research uses quantitative descriptive methods. The population in this study were all level 2 students of the D3 Nursing study program, and the sample was taken using the N / 1 + N(e²) formula, namely 60 respondents and the sample collection technique used was simple random sampling by taking respondents randomly/drawn based on class A, B, and C. The instrument used as a measuring tool is a questionnaire. Results: The results showed that 28 respondents (46.67%) had good knowledge, 12 respondents (20%) had sufficient knowledge, and 20 respondents (33.33%) had less knowledge. Conclusion: most of the knowledge of level 2 nursing students about physical activity is good 46.67% at ITSK dr Soepraoen Hospital Malang.